Covid-19 and Bell Palsy: Could it Be Neurotrophic Involvement? - Kemal Koray Bal; Sedat Alagöz; Talih Özdaş; Asiye Merve Erdoğan; Vedat Delibaş; Gülali Ocar; Okan Dilek; Feride Fatma Görgülü; Orhan Görgülü (The Turkish Journal of Ear Nose and Throat)
Objective: Idiopathic cases are common, and the etiology is not clearly explained. The purpose of this study is to compare the frequency, clinical-radiological characteristics and response to the treatment of peripheral facial paralysis patients who visited the otorhinolaryngology clinic during the Covid-19 pandemic and in the same period of the previous year, and to discuss this data in the light of the literature.Materials and Methods: Otoscopic examination findings, audiological results, application and post-healing grade information according to House Brackmann Staging system were obtained from all the patients’ files. Temporal Bone Computed Tomography, which is included in the routine practice of our clinic, and Cranial & Diffusion Magnetic Resonance Imaging examinations for the elimination of central causes were applied to the patients. Facial nerve tympanic, mastoid, labyrinth segment and geniculate ganglion diameters were measured separately for the diseased side and the healthy side.Results: In the study, Group 1 consisted of 42 patients (43%), and Group 2 consisted of 56 patients (57%). 56 (57%) of the patients were male and 42 (43%) were female. The left and right-side facial paralysis admissions were equal, but no statistically significant difference was found (p=0.068).Conclusions: Peripheral facial paralysis is a very common case in ear, nose, and throat practice and requires priority treatment and follow-up. Since the Covid-19 virus is a new entity for the world, we think that it has a neurotrophic affinity for the facial nerve although our knowledge about this virus is limited.